New adhesive traps to monitor urban mosquitoes with a case study to assess the efficacy of insecticide control strategies in temperate areas - Beniamino Caputo; Annamaria Ienco; Mattia Manica; Vincenzo Petrarca; Roberto Rosà; Alessandra della Torre (Parasites & Vectors, 2015)
Abstract Background Urban mosquitoes in temperate regions may represent a high nuisance and are associated with the risk of arbovirus transmission. Common practices to reduce this burden, at least in Italian highly infested urban areas, imply calendar-based larvicide treatments of street catch basins – which represent the main non-removable urban breeding site – and/or insecticide ground spraying. The planning of these interventions, as well as the evaluation of their effectiveness, rarely benefit of adequate monitoring of the mosquito abundance and dynamics. We propose the use of adhesive traps to monitor Aedes albopictus and Culex pipiens adults and to evaluate the efficacy of insecticide-based control strategies. Methods We designed two novel types of adhesive traps to collect adult mosquitoes visiting and/or emerging from catch basins. The Mosquito Emerging Trap (MET) was exploited to assess the efficacy of larvicide treatments. The Catch Basin Trap (CBT) was exploited together with the Sticky Trap (ST, commonly used to collect ovipositing/resting females) to monitor adults abundance in the campus of the University of Rome “Sapienza” - where catch basins were treated with Insect Growth Regulators (IGR) bi-monthly and Low-Volume insecticide spraying were carried out before sunset - and in a nearby control area. Results Results obtained by MET showed that, although all monitored diflubenzuron-treated catch basins were repeatedly visited by Ae. albopictus and Cx. pipiens, adult emergence was inhibited in most basins. Results obtained by ST and CBT showed a significant lower adult abundance in the treated area than in the untreated one after the second adulticide spraying, which was carried out during the major phase of Ae. albopictus population expansion in Rome. Spatial heterogeneities in the effect of the treatments were also revealed. Conclusions The results support the potential of the three adhesive traps tested in passively monitoring urban mosquito adult abundance and seasonal dynamics and in assessing the efficacy of control measures. ST showed higher specificity for Ae. albopictus and CBT for Cx. pipiens. The results also provide a preliminary indication on the effectiveness of common mosquito control strategies carried out against urban mosquito in European urban areas.